Analisis Risiko Keselamatan dan Kesehatan Kerja (K3) melalui Program CARE di Proyek Trans Icon Surabaya PT Total Bangun Persada Tbk Tahun 2022 - Robbidi, Kamran; Yaser, Muhamad; Marwanto (Journal of Public Health Education, 2024)
Introduction: According to BPJS Employment in 2020, the number of work accidents has reached 153,044 cases. This figure decreased by 1.46% compared to 2019, namely 155,327 cases. Objectives: To analyze occupational safety and health (K3) risks through the CARE program at PT Total Bangun Persada Tbk's Surabaya Trans Icon Project in 2022. Method: This research uses a qualitative approach. The researcher is the main instrument in this research, but to obtain the required data, he is assisted by instruments in the form of interview guides, related documents, cell phones, recording equipment, and HIRADC sheets.  There were three research informants.  Data analysis in this research includes data reduction, data presentation, and conclusion. Results: There were 59 hazard identifications from 20 sources of danger in the Trans Icon Surabaya project work of PT Total Bangun Persada Tbk, where the risk values ​​were obtained for the low-risk low-risk (11.9%), medium-risk category (15.3%), high-risk category ( 20.3%), and the extreme risk category (52.5%). Conclusion: the CARE program policy implemented at PT Total Bangun Persada Tbk aims to create a safe and healthy work environment as well as protect employees and maintain both physical and mental conditions so that employees can work safely and comfortably. Researchers provide recommendations for companies in planning for potential hazards and controlling the risk of work accidents to increase work productivity and worker welfare through the CARE program.